2004
DOI: 10.2134/agronj2004.1216
|View full text |Cite
|
Sign up to set email alerts
|

Sod‐Seeding and Grazing Effects on Alfalfa Weevils, Weeds, and Forage Yields in Established Alfalfa

Abstract: Alfalfa (Medicago sativa L.) hay production for dairy and equine industries is a profitable enterprise in the Great Plains. However, as stands thin, forage production decreases and weeds increase, resulting in decreased returns. The objective of this research was to determine if alternative management strategies using October sod seeding plus March grazing could be utilized to increase forage production and control pests. Experiments were conducted at four locations in central Oklahoma from 1998–2000. Two ungr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…This is to be expected given that the second cutting was taken during the period in spring (mid-May) when annual ryegrass is most productive at this location. The reduction in alfalfa yields in the spring harvests were similar to that observed by Cummings et al (5) and in Wisconsin for alfalfa established with annual ryegrass as a nurse crop (9). Within the CR-AR treatment, the yield contribution of the overseeded species was predominantly (>75% in each year) AR herbage (data not shown).…”
Section: Competition Between Alfalfa and The Overseeded Cropsupporting
confidence: 87%
“…This is to be expected given that the second cutting was taken during the period in spring (mid-May) when annual ryegrass is most productive at this location. The reduction in alfalfa yields in the spring harvests were similar to that observed by Cummings et al (5) and in Wisconsin for alfalfa established with annual ryegrass as a nurse crop (9). Within the CR-AR treatment, the yield contribution of the overseeded species was predominantly (>75% in each year) AR herbage (data not shown).…”
Section: Competition Between Alfalfa and The Overseeded Cropsupporting
confidence: 87%
“…Majak et al (2003) found that cattle fed a diet of 100% alfalfa became bloated 105 times over a 2-yr study period while those fed a 50% orchardgrass-alfalfa mix bloated only twice. Weed suppression may be another important benefit of mixtures over monoculture stands (Cummings et al, 2004). Grasses mixed with alfalfa also have been shown to reduce insect pests like alfalfa weevil Hypera postica (Coleoptera: Curculionidae), as well as potato leaf hopper Empoasca fabae (Hemiptera: Cicadellidae) infestations in young stands (Lamp, 1991;Roda et al, 1996).…”
Section: Evaluation Of Alfalfa-tall Fescue Mixtures Across Multiple Ementioning
confidence: 99%
“…Grasses mixed with alfalfa also have been shown to reduce insect pests like alfalfa weevil Hypera postica (Coleoptera: Curculionidae), as well as potato leaf hopper Empoasca fabae (Hemiptera: Cicadellidae) infestations in young stands (Lamp, 1991;Roda et al, 1996). Weed suppression may be another important benefit of mixtures over monoculture stands (Cummings et al, 2004). From an energy balance perspective, legumebased pastures can supply sufficient N through fixation to supply grazing animals with enough protein and energy to sustain weight gains with much less external energy expenditure and greenhouse gas emission than fertilized grass pasture (Chen et al, 2004).…”
Section: Evaluation Of Alfalfa-tall Fescue Mixtures Across Multiple Ementioning
confidence: 99%
“…Also, weed seeds remain on the soil surface during the alfalfa interval because the field is not tilled; consequently, weed seed survival declines rapidly across time, as noted in Figure 2. Alfalfa competitiveness with weeds decreases in the later years because stand density of alfalfa declines across time 14,15 . 4).…”
Section: Interval Of Alfalfamentioning
confidence: 99%